2020
DOI: 10.12933/therya-20-1008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of caves as bat roosts in the brazilian-paranense biogeographic region of Bolivia

Abstract: Bats play vital roles in nature as pollinators, seed dispersers, and natural controllers of insect pests. They serve as indicators of habitat disturbance and provide an insight into the health status of an ecosystem. This enormous importance contrasts with the lack of information on the current state of their roosts in Bolivia, particularly as regards caves and caverns. A search for caves and caverns was carried out in the eastern department of Santa Cruz, Bolivia, corresponding to the Brazilian-Paranense biog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 11 publications
1
4
0
8
Order By: Relevance
“…Bats population in Sanghyang Kenit was distributed from twilight to dark zones, which generated guano piles on the cave floor. Commensurate with cave crickets, bats prefer humid and dark places for their roosting sites (Furey & Racey 2016;Lizarro et al 2020;Newman et al 2021). The measurement of soil pH showed that twilight and dark zones have more acidic pH than the entrance.…”
Section: Habitat Preference Based On Environmental Parametersmentioning
confidence: 99%
“…Bats population in Sanghyang Kenit was distributed from twilight to dark zones, which generated guano piles on the cave floor. Commensurate with cave crickets, bats prefer humid and dark places for their roosting sites (Furey & Racey 2016;Lizarro et al 2020;Newman et al 2021). The measurement of soil pH showed that twilight and dark zones have more acidic pH than the entrance.…”
Section: Habitat Preference Based On Environmental Parametersmentioning
confidence: 99%
“…Na BAP, foi registrada no planalto, nas regiões de Bonito, Miranda, Cuiabá, Corixo Grande, Tucavaca, Bolívia e Paraguai; e na planície, nas regiões de Nabileque e Miranda (E. Gonçalves & Gregorin, 2004;E. Fischer et al, 2015;Bordignon & Shapiro, 2018;Lizarro et al, 2020). Utiliza ambientes florestais associados a corpos d'água.…”
Section: Gênero Peropteryx Peters 1867unclassified
“…Oliveira, 2016;Silveira, 2016;Bordignon & Shapiro, 2018;N. Carvalho, 2017;Lizarro et al, 2020;Silveira et al, 2020;C. Santos et al, 2021).…”
Section: Gênero Desmodus Wied-neuwied 1826unclassified
See 1 more Smart Citation
“…Na BAP, foi registrada no planalto, nas regiões de Bonito, Miranda, Cuiabá, Corixo Grande, Tucavaca, Bolívia e Paraguai; e na planície, nas regiões de Nabileque e Miranda (E. Gonçalves & Gregorin, 2004;E. Fischer et al, 2015;Bordignon & Shapiro, 2018;Lizarro et al, 2020). Utiliza ambientes florestais associados a corpos d'água.…”
Section: Gênero Peropteryx Peters 1867unclassified